Student Travel Behavior Of Grab App Users In Yogyakarta Urban Area - Monika Stelamaris Mao Sila; Mutiasai Kurnia Devi; Iwan Aminto Ardi (Universitas Islam Sultan Agung Semarang, 2023)
Urban areas are usually limited by territorial restrictions so the available space is very limited. The limited space of the area is crowded with various community activities that are reflected in the allocation and use of land. With the divided territory into various land allocations, to do different activities requires movement between regions. The existence of online application-based transportation also plays a role in changing the form of people's travel behavior in Yogyakarta which of course increases in line with the ease of transportation offered. This study aims to determine the characteristics of the movement of online application-based transportation users based on the purpose of travel conducted by students and the samples taken are students of the campus of Universitas Sarjanawiyata Tamansiswa (UST), Gadjah Mada University Yogyakarta (UGM) and Muhammadiyah University yogyakarta (UMY) where these three campuses were chosen because they are considered able to represent the entirety of the total students in the Yogyakarta Urban Area. The analysis used in this research is descriptive statistical analysis, chi square analysis and fisher's exact test and also and one-way anova analysis. The results of the analysis showed a relationship between the location of residence and the purpose of travel and mileage and costs that were disbursed and there were differences for the purpose of travel conducted by students based on the location of residence.Keywords: Online Transportation, Travel Behavior, Student Grab Users